2009
DOI: 10.1007/s10597-009-9227-2
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Cultural Equivalence of HSCL-25 and WHO (ten) Wellbeing Index: Findings From a Population-Based Survey of Immigrants and Non-Immigrants in Sweden

Abstract: The aim of this study was to investigate whether the Hopkins Symptom Checklist (HSCL-25) and the WHO (ten) Wellbeing Index are cross-culturally equivalent by comparing Scandinavians with Middle Eastern immigrants in Sweden. The study population consisted of a stratified random sample of native-born Swedes and immigrants from Finland, Iraq and Iran. Both instruments loaded on a single factor in the respective populations. A few of the items did however not discriminate or predict equally well in the groups, non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 51 publications
0
35
0
Order By: Relevance
“…the Harvard Trauma Questionnaire (HTQ-30; Mollica et al 1992), a 30-item transculturally validated screening instrument for post-traumatic stress disorder (PTSD) symptomatology (Cronbach's a 00.96 in the current sample); the Hopkins Symptom Checklist (HSCL-25; Mollica et al 1996), which measures anxiety (10 items) and depression symptoms (15 items) and has proven to be useful as a screening instrument in several cross-cultural studies and patient studies (Hansson et al 1994;Kleijn et al 1998;Tinghog and Carstensen 2010) (Cronbach's a 00.96 for the total HSCL-25 score); the COPE-Easy (Carver, Scheier and Weintraub. 1989), which measures different coping styles by means of 32 items (Cronbach's a varying between 0.67 for avoidance behaviour and 0.91 for active problem-directed coping); and the Lowlands Acculturation Scale (LAS; Mooren et al 2001), which assesses the level of cultural adaptation with 20 items and distinguishes between a global orientation towards the past (and land of origin) as opposed to the orientation towards the future (and country of current residence) in terms of integration skills and culture bound traditions (Cronbach's a for the subscales varies between 0.61 and 0.69).…”
Section: Instrumentsmentioning
confidence: 92%
“…the Harvard Trauma Questionnaire (HTQ-30; Mollica et al 1992), a 30-item transculturally validated screening instrument for post-traumatic stress disorder (PTSD) symptomatology (Cronbach's a 00.96 in the current sample); the Hopkins Symptom Checklist (HSCL-25; Mollica et al 1996), which measures anxiety (10 items) and depression symptoms (15 items) and has proven to be useful as a screening instrument in several cross-cultural studies and patient studies (Hansson et al 1994;Kleijn et al 1998;Tinghog and Carstensen 2010) (Cronbach's a 00.96 for the total HSCL-25 score); the COPE-Easy (Carver, Scheier and Weintraub. 1989), which measures different coping styles by means of 32 items (Cronbach's a varying between 0.67 for avoidance behaviour and 0.91 for active problem-directed coping); and the Lowlands Acculturation Scale (LAS; Mooren et al 2001), which assesses the level of cultural adaptation with 20 items and distinguishes between a global orientation towards the past (and land of origin) as opposed to the orientation towards the future (and country of current residence) in terms of integration skills and culture bound traditions (Cronbach's a for the subscales varies between 0.61 and 0.69).…”
Section: Instrumentsmentioning
confidence: 92%
“…The HSCL-25 [49] is a valid cross-cultural measure of depression and anxiety [50,51,52,53,54,55,56]. The first 10 items of the questionnaire concern anxiety, while the remaining 15 items relate to depression.…”
Section: Methodsmentioning
confidence: 99%
“…Hence, the use of the HSCL-25 would investigate the models using a different screening questionnaire. The HSCL-25 has been validated in clinical and general population samples in developed and developing countries including the Arab world [49,50,51,52,53,54]. It is important to use the HSCL-25 to assess the models for the following reasons.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A 2009 study in Sweden showed that HSCL-25 had comparable results between subjects from a Scandinavian population and subjects from a population of immigrants from the Middle East [27]. This study suggested that HSCL-25 could be used for population surveys within multicultural groups in western Europe [28]. HSCL-25 has been used and tested many times in primary care situations, compared with the diagnosis of psychiatric disorder carried out by Primary Care practitioners [29] [30].…”
Section: Discussionmentioning
confidence: 92%